2018
DOI: 10.3390/ijms19113360
|View full text |Cite
|
Sign up to set email alerts
|

T-2 Toxin Exposure Induces Apoptosis in TM3 Cells by Inhibiting Mammalian Target of Rapamycin/Serine/Threonine Protein Kinase(mTORC2/AKT) to Promote Ca2+Production

Abstract: Although mTOR (the mammalian target of rapamycin) can regulate intracellular free Ca2+concentration in normal cultured podocytes, it remains elusive as to how mTORC2/AKT-mediated Ca2+participates in the process of T-2 toxin-induced apoptosis. The potential signaling responsible for intracellular Ca2+ concentration changes was investigated using immunoblot assays in an in vitro model of TM3 cell injury induced by T-2 toxin. Changes in Ca2+ were assessed using the Ca2+-sensitive fluorescent indictor dye Fura 2-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
(44 reference statements)
2
9
0
Order By: Relevance
“…Although Nrf2 has been reported as a pivotal regulator against T-2 toxin-induced oxidative stress [ 7 , 45 ], how T-2 toxin inhibited the expression of Nrf2 is still unclear. In this study, T-2 toxin significantly decreased the expression of Nrf2 in MCF-7 cells ( Figure 2 ), which was consistent with the results in other cells [ 1 , 35 , 37 ]. Importantly, we found that the downregulation of Nrf2 under T-2 toxin stress is mediated by ATF3 ( Figure 5 ), which provided new insight into the regulatory mechanism of Nrf2 underT-2 toxin stress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although Nrf2 has been reported as a pivotal regulator against T-2 toxin-induced oxidative stress [ 7 , 45 ], how T-2 toxin inhibited the expression of Nrf2 is still unclear. In this study, T-2 toxin significantly decreased the expression of Nrf2 in MCF-7 cells ( Figure 2 ), which was consistent with the results in other cells [ 1 , 35 , 37 ]. Importantly, we found that the downregulation of Nrf2 under T-2 toxin stress is mediated by ATF3 ( Figure 5 ), which provided new insight into the regulatory mechanism of Nrf2 underT-2 toxin stress.…”
Section: Discussionsupporting
confidence: 92%
“…[ 33 , 34 ]. Previous studies showed that oxidative stress is associated with a lot of its toxic effects [ 35 ]. However, the molecular mechanism of T-2 toxin-induced oxidative stress is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, T-2 toxin signi cantly decreased the expression of Nrf2 in MCF-7 cells (Fig. 2), which was consistent with the results in other cells [1,40,42]. Importantly, we found that the downregulation of Nrf2 under T-2 toxin stress is mediated by ATF3 (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…[38,39]. Previous studies showed that oxidative stress is associated with a lot of its toxic effects [40]. However, the molecular mechanism of T-2 toxin induced oxidative stress is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, T-2 can inhibit mammalian target of rapamycin 2 (mTORC2)/Akt signaling in mouse TM3 Leydig cells and increase free Ca 2+ concentration in cells, which may explain why the toxin induces cell apoptosis. Therefore, in addition to mTOR activators, the use of Ca 2+ chelators can prevent apoptosis under these conditions (Wang et al 2018a). Based on the above, T-2 stimulated the caspase-mediated mitochondrial apoptosis pathway by inhibiting protein synthesis and inducing DNA damage caused by oxidative stress, which is an indispensable mechanism for inducing apoptosis (Chaudhari et al 2009).…”
Section: Autophagy and Apoptosismentioning
confidence: 99%